The Effect of Foreign Direct Investment (FDI) Strategy: a case of China National Petroleum Corporation in Sudan Republic - Jiang, Yang (2012)
Since the rapid development in China’s economy, the oil consumption of Chinese market is rising，the consumption of the oil contains various industries: oil exploration, vehicle production, taxi industry, and spinach industry, the gap between oil supply and demand is growing and the China’s oil imports increase year by year. So it is very significant to discuss the overseas foreign direct investment for China’s oil export, the dissertation is about the Chinese international companies’ global direction, particularly Chinese oil industry. Among these, the particular attention would be given to China National Petroleum Corporation (CNPC) which is one of the biggest and outstanding Chinese petroleum companies and its current internationalization strategy resulted in hot discussion. The mission of this study is to discover the reasons behind internationalization process of Chinese petroleum companies based on the example of CNPC in Sudan Republic, its environment selection and entry modes applied by petroleum companies.